Isolation And Characteristics Of Lactic Acid Bacteria In Feces Of Jember Local Mongoose - Kukuh Munandar; Dina Afriayanti; Inayatul Karimah (International Applied Science, 2022)
Drinking a cup of coffee is not only a matter of taste but also a part of Indonesian’s daily life. Coffee shops which have proliferated so far proves this lifestyle. One of the best selling coffee bean products is mongoose coffee. It is a product of coffee beans which have been swallowed by mongoose and through its digestive tract. In the digestive tract, beans are being fermented by microbes (lactic acid bacteria or LAB). This fermentation process contributes to the unique taste and aroma of the coffee. The taste and aroma are very appealing to coffee lovers, resulting in the rise of demands in both local and international markets in every year. However, this leads to the escalation of mongoose hunting, threatening the population of mongoose (Paradoxurus hermaphroditus). Moreover, its limited digesting capacity also hinders the production of mongoose coffee. The present study offers an alternative to produce mongoose coffee by optimizing in-vitro fermentation which simulates the natural process of fermentation inside mongoose’s digestive organs. This in-vitro fermentation uses bacteria isolate (LAB) from mongoose’s feces collected from the local society of Jember. The study, therefore, aimed to: 1) isolate LAB from mongoose’s feces, and 2) identify the characteristics of collected LAB. Based on the result of data analysis, it was concluded that 5 LAB isolates from local mongoose’s feces were identified, namely: LAB-1 is Lactobacillus plantarum, LAB-2 is Lactobacillus brevis, LAB-3 is Leuconostoc paramesenteroides, LAB-4 is Leuconostoc mesenteroides, and LAB-5 is Streptococcus faecium